Barriers and Motivators to Being Physically Active for Older Home Care Clients. (18th February 2013) - Burton, Elissa; Lewin, Gill; Boldy, Duncan
ABSTRACT: The aim of the study was to identify the motivators and barriers to being physically active for older people receiving either restorative or "usual" home care services. The study used a mixed method descriptive design including questionnaire and interviews. Questionnaires were sent to 1, 490 clients who received either service between 2006–2009; 506 (34%) responded, and 190 indicated willingness to participate in a follow-up interview. Of the latter, 20 were purposively selected and interviewed. "Well-being" and "health and fitness" were the top two reasons participants gave for being active. "Ongoing injury/illness" and feeling "too old" were the highest ranked barriers. The qualitative findings confirmed that older home care clients know physical activity is good for health and well-being, however, due to ongoing injury/illness and thinking they are too old, they may not be as active as they could be. This may impact on the number of home care services older people need over the longer term.